2021
DOI: 10.1108/rpj-03-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 3D printing process parameters on the mechanical properties and mass of PLA parts and predictive models

Abstract: Purpose This paper aims to evaluate the influence of the parameters of the Fused Filament Fabrication (FFF) process on the mechanical properties and on the mass of parts printed in Polylactic Acid (PLA). In addition, the authors developed predictive models for the analysed responses. Design/methodology/approach A full Factorial type of experimental planning method was used to define the conditions for manufacturing parts according to the variation of the construction parameters, extrusion temperature and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…However, it displays some limitations such as poor water solubility, and being frangible [19]. Owing to its good accessibility, PLA is currently one of the most broadly applicable biodegradable polymers for various uses in packaging, electronic industries, automotive industries, and prosthesis fabrication, substituting effectively for petroleum-based polymers [20,21]. Many trends in orthopedic practice and research have suggested that PLA is safe and nontoxic [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, it displays some limitations such as poor water solubility, and being frangible [19]. Owing to its good accessibility, PLA is currently one of the most broadly applicable biodegradable polymers for various uses in packaging, electronic industries, automotive industries, and prosthesis fabrication, substituting effectively for petroleum-based polymers [20,21]. Many trends in orthopedic practice and research have suggested that PLA is safe and nontoxic [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several DOE approaches have been utilized to optimize the process parameters of the FFF system, including the Taguchi method, analysis of variance (ANOVA), complete factorial designs, bacterial foraging technique, and fuzzy logic because many parameters might impact the printing process, the default configuration of printing process parameters provided by manufacturers cannot guarantee the quality of printed products [32]. Extensive research is being conducted to determine the impact of various FFF process parameters on the different responses [33][34][35][36]. The Taguchi design method provides a practical approach to lower cost, higher quality, and performance optimization.…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…At the same time, PLA is a thermoplastic with rigid, strong, and is easy to process characteristics, making it highly popular in AM applications. PLA can also be used as an implant material in the health sector [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%